If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2)(3x + -6) = (x + 1)(3x + -4) Reorder the terms: (2 + x)(3x + -6) = (x + 1)(3x + -4) Reorder the terms: (2 + x)(-6 + 3x) = (x + 1)(3x + -4) Multiply (2 + x) * (-6 + 3x) (2(-6 + 3x) + x(-6 + 3x)) = (x + 1)(3x + -4) ((-6 * 2 + 3x * 2) + x(-6 + 3x)) = (x + 1)(3x + -4) ((-12 + 6x) + x(-6 + 3x)) = (x + 1)(3x + -4) (-12 + 6x + (-6 * x + 3x * x)) = (x + 1)(3x + -4) (-12 + 6x + (-6x + 3x2)) = (x + 1)(3x + -4) Combine like terms: 6x + -6x = 0 (-12 + 0 + 3x2) = (x + 1)(3x + -4) (-12 + 3x2) = (x + 1)(3x + -4) Reorder the terms: -12 + 3x2 = (1 + x)(3x + -4) Reorder the terms: -12 + 3x2 = (1 + x)(-4 + 3x) Multiply (1 + x) * (-4 + 3x) -12 + 3x2 = (1(-4 + 3x) + x(-4 + 3x)) -12 + 3x2 = ((-4 * 1 + 3x * 1) + x(-4 + 3x)) -12 + 3x2 = ((-4 + 3x) + x(-4 + 3x)) -12 + 3x2 = (-4 + 3x + (-4 * x + 3x * x)) -12 + 3x2 = (-4 + 3x + (-4x + 3x2)) Combine like terms: 3x + -4x = -1x -12 + 3x2 = (-4 + -1x + 3x2) Add '-3x2' to each side of the equation. -12 + 3x2 + -3x2 = -4 + -1x + 3x2 + -3x2 Combine like terms: 3x2 + -3x2 = 0 -12 + 0 = -4 + -1x + 3x2 + -3x2 -12 = -4 + -1x + 3x2 + -3x2 Combine like terms: 3x2 + -3x2 = 0 -12 = -4 + -1x + 0 -12 = -4 + -1x Solving -12 = -4 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -12 + x = -4 + -1x + x Combine like terms: -1x + x = 0 -12 + x = -4 + 0 -12 + x = -4 Add '12' to each side of the equation. -12 + 12 + x = -4 + 12 Combine like terms: -12 + 12 = 0 0 + x = -4 + 12 x = -4 + 12 Combine like terms: -4 + 12 = 8 x = 8 Simplifying x = 8
| 2.3/x=5.2 | | x-(3x+4)=5-(4x+3) | | 10=3v-17 | | n-n=-4(2n-8)+8(n+12) | | 25=a(30-0)(30-60) | | x-56=64 | | -6+3(1-9v)=-24 | | x-32=28 | | 190+b=200b | | (x+5)*28=2x*21 | | 10x-22=8x+12 | | x*ln(x)=(ln(3))/3 | | (x+5)*28=2x+21 | | x^2+y^2-12x+4y=24 | | x+5*28=2x+21 | | s^2+20+4s= | | 4x=44p-16 | | 4m-30+m=3m+4 | | 3(-16+7x)-15x= | | 20*(20+x)=15*(15+3x) | | 6+17(-10-8g)= | | 2q-5=7q | | 75+2=15+5 | | 11-3x+6y=0 | | P(n)=3n | | 10a-7(-17a-13)= | | (x*x)=(x-2)*(x+2) | | 21+5=15+11 | | X*12=6*(x+4) | | y=-0.2*36+50 | | 2x+53+68=75 | | k/5-9=-17 |